Update on polymers for pulmonary drug delivery - Smyth, Hugh D. C. (Smithers Rapra Technology Ltd., 2013)
Pulmonary drug delivery has been a rapidly expanding field, moving from the traditional propellant based metered dose inhaler delivery of small asthma drugs, to a broader landscape of new devices and novel drugs for local and systemic delivery. The field has greatly expanded yet the tools for pulmonary drug delivery systems have not kept pace with the potential applications. One of the key developments has been the use of polymers to achieve better control of pulmonary drug delivery. This has the potential to expand the toolbox available for researchers in the field to deliver their new chemic.